2023
DOI: 10.1021/jacs.3c04027
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Pyroptosis Using AIEgen-Based sp2 Carbon-Linked Covalent Organic Frameworks

Abstract: Covalent organic frameworks (COFs) have emerged as a promising class of crystalline porous materials for cancer phototherapy, due to their exceptional characteristics, including light absorption, biocompatibility, and photostability. However, the aggregation-caused quenching effect and apoptosis resistance often limit their therapeutic efficacy. Herein, we demonstrated for the first time that linking luminogens with aggregation-induced emission effect (AIEgens) into COF networks via vinyl linkages was an effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 46 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…The COF-triggered pyroptosis significantly boosted the proportion of T-cell infiltration and diminished the number of immunosuppressive T reg -cells. Moreover, in combination with an αPD-1 blockade therapy COF, COF-mediated pyroptosis eliminated primary and distant tumors as well as prevented recurrence in a 4T1 tumor model …”
Section: Self-assembled Microporous Nanomaterialsmentioning
confidence: 99%
“…The COF-triggered pyroptosis significantly boosted the proportion of T-cell infiltration and diminished the number of immunosuppressive T reg -cells. Moreover, in combination with an αPD-1 blockade therapy COF, COF-mediated pyroptosis eliminated primary and distant tumors as well as prevented recurrence in a 4T1 tumor model …”
Section: Self-assembled Microporous Nanomaterialsmentioning
confidence: 99%
“…[170d] Phototherapy is an effective stimulus for ICD, as confirmed using various COF systems. [170,[174][175] These systems use photosensitizing COFs to damage tumor cells via ROS generation or hyperthermia; the tumor cells then release DAMPs that activate antitumor immunity. In 2022, Sun and colleagues [170d] reported that COF-618-Cu, which exhibits CAT-like and glutathione peroxidase (GPX)-mimicking activity, enhances PDT and PTT by decomposing H 2 O 2 and oxidizing GSH, thereby eliciting a strong ICD response and remodeling the immune microenvironment (Figure 12C).…”
Section: Synergistic Immunotherapymentioning
confidence: 99%
“…[120] Integrating luminogens with aggregation-induced emission effect into COF networks through vinyl ligations is an effective method to create nonmetallic pyroptosis inducers, ultimately boosting antitumor immunity (Figure 10a). [70] The formation of vinyl bonds in AIE COF results in high brightness, and strong light absorp-tion, which promotes the production of reactive oxygen species that causes pyroptosis (Figure 10b,c). In addition, A COF-919 is synthesized using a flat and distorted Aiegen-based motif.…”
Section: Mesoporous Materials Have Seen An Increase In Use For Cancer...mentioning
confidence: 99%